Kuliah Kerja Nyata: Membangun Generasi Muda Cerdas dan Kreatif, Serta Memperbaiki Desa Berkualitas, dan Edukasi Perpajakan pada Gen Z di Desa Lubang Buaya, Setu, Kab. Bekasi - Elia Rossa; Dea Maharani; Elsa Natali; Amelia Destiyana; Shafa Audina Sukmaningrum; Aldila Sukaputri Irmadani; Najwa Balqis; Inday Hardika; Marta Marta (Jurnal Riset Akuntansi, 2024)
The Real Work Lecture Program (KKN) has been implemented in Lubang Buaya Village, Setu, Kab. Bekasi. In this program we seek to help local communities overcome the problems in the economic, educational, social and health sectors as well as in the infrastructure and environmental sectors that they face. This article discusses KKN's efforts to develop the potential of the younger generation, especially Generation Z, through strengthening intelligent and creative education. Apart from that, this article also highlights improvements to village facility infrastructure to improve the quality of life of local communities. During KKN activities, various tax education programs are carried out to increase public understanding and awareness, especially generation Z, about the obligations and benefits of taxation. Through the integration of these activities, it is hoped that a young generation can be created that is not only intelligent and creative, but also has social awareness and the ability to contribute to sustainable village development.